KONTRIBUSI DUKUNGAN ORANGTUA DAN TEMAN SEBAYA TERHADAP ORIENTASI KARIER PADA FASE EMERGING ADULTHOOD - Shafira Maharani Putri Santoso, - (2021)
Emerging adulthood is a transition from adolescence to adulthood where individuals experience new responsibilities to determine their career orientation. This study aims to examine the contribution of parent support and peer support toward career orientation in emerging adulthood. Respondents (N=307) aged 18-29 years old filled out the career orientation scale questionnaire to measure career orientations, career-related parent support questionnaire in the field parental supports, and career-related peer support in the field peer supports. The sampling technique used rules of thumbs technique. The data analysis technique used is multiple regression analysis to see the effect of parental support and peer support on career orientations in emerging adulthood. The results of this study indicate that parental support and peer support are give contribution to career orientation in emerging adulthood. Keywords: Career orientation; emerging adulthood; peer support; parental support.